Cotton seed systems in Africa: overview of the present situation and prospects for improvement - (:unkn) unknown (My University, 2021)
In Africa, cotton is grown in 28 countries, on 4.3 Million smallholder cotton farms. It covers 4.5 Million ha – mainly rainfed, producing 1.8 Million tons of fibre, representing 7% of the world cotton fibre production. Albeit small contribution to world cotton supply, cotton is a crop of major social and economic importance in Africa. As a cash crop, it is an important source of income for over 20 million people living in rural areas, providing cash flow for essentials, and an important source of industrial jobs and foreign exchange. In addition, it is a lead crop in cropping systems that also include food crops. African cotton production suffers from some of the lowest lint yields: while the world average is 778 kg/ha, it is only 300-400 kg/ha in francophone, Eastern and Southern Africa. This yield gap is attributed to (i) environmental and cultural conditions, (ii) irregular investment in R&D, and (iii) low rotation of (obsolete) varieties and poor seed quality. The African cotton sector is characterized by a diversity of actors and situations. Major stakeholders involved in the cotton sector are cotton producers and their associations, public and private cotton companies, public and private agricultural research organisations, inter-professional associations, seed producers, distributors and retailers, Ministries of Agriculture and their seed inspection services, plant protection services… The cotton sector is organized either as a monopoly (a single cotton company), an oligopoly (a limited number of cotton companies, coordinated by an inter-professional association), or based on an open market. The price of seed cotton is set by a national coordination system or independently by the cotton companies. Currently, in Africa, the organization of the cottonseed sector is considered as an important bottleneck to increase the yields, the quantity and quality of seed cotton and fiber, the income of cotton producers, and the profitability of the
Keywords: African Research